An Analysis of Speech Acts and Politeness Strategies Used by The English Native Speaker (ENS) Teacher and Local Teachers in English Teaching and Learning at Dyatmika Kindergarten - ., MADE WINNY PARAMITHA; ., DRS. I WAYAN SUARNAJAYA, M.A., P.hD; ., DR. I GEDE BUDASI, M.Ed.DIP APPLIN (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2016)
This study aimed at finding out (1) types of speech acts produced by the English native teacher and local teachers in English teaching and learning activities, (2) the differences in terms of speech acts used by the English native teacher and local teachers in teaching and learning English, (3) the English native teacher and local teachers? reasons in using certain types of speech acts in teaching and learning English, (4) the types of politeness strategies produced by the English native teacher and local teachers in teaching and learning English, (5) the differences in terms of politeness strategies used by the English native teacher and local teachers in teaching and learning English, and (6) the English native teacher and local teachers? reasons in using certain types of politeness strategies in teaching and learning English. This study was carried out at Dyatmika Kindergarten as a school with bilingual program. This study used a descriptive qualitative design. Observation, questionnaire and interview were the methods of data collection. The data were analyzed by using Speech Acts Theory by Searle (1999) and Politeness Strategies by Brown and Levinson (1987). The results indicated that both the English native teacher and local teachers mostly used directives in the classroom to get the students to behave in the way that is expected by the teacher. Moreover, the English native teacher mostly used positive politeness in the classroom to build students? self-esteem and enthusiasm in learning. Besides, the local teachers mostly used positive politeness to build students? motivation in learning and get the students involved in classroom discussion. Also it was found that there were several aspects affecting the teachers in using certain speech acts and politeness strategies. keyword : speech acts, politeness strategies